Test uptake and hepatitis C prevalence in 5483 Danish people in drug use treatment from 1996 to 2015: a registry‐based cohort study. (25th November 2018) - Øvrehus, Anne; Nielsen, Stine; Hansen, Janne Fuglsang; Holm, Dorte Kinggaard; Christensen, Peer
Abstract: Background and aims: The aims of this study were, in people in treatment for drug use in Funen, Denmark, to: (1) assess prevalence of hepatitis C virus (HCV) test uptake and prevalence of HCV; (2) identify predictors of test update and HCV infection; and (3) characterize changes between 1996 and 2015 in test uptake, HCV prevalence and drug use. Design: Cohort study linking the Danish National Registry on Drug Users in Treatment to the regional hepatitis test registry and the Danish Death Certificate Registry, thus combining longitudinal data on drug use with data on HCV testing and results. Setting and participants: People recorded as having received treatment for drug use between 1996 and 2015 ( n = 5483) in Funen, Denmark. In the cohort, 24.8% were female, median age 23 years [interquartile range (IQR) = 20–32] at entry and 50% had self‐reported injecting or had received opiate substitution therapy (OST). Measurements: The main outcomes were the test for HCV ever and latest HCV‐RNA being positive. The main predictors were for test and infection investigated; ever receiving OST, self‐reported injecting, age at entry and connection to treatment centre offering outreach hepatitis care. Findings: HCV test uptake was 52% and prevalence of current HCV‐RNA+ was 21% in people alive at the end of follow‐up. Positive predictors of having undergone HCV testing were: receiving OST [odds ratio (OR) = 3.7; 95% confidence interval (CI) = 3.2–4.5], self‐reported injecting (OR = 2.3; 95% CI = 2.0–2.7), female gender (OR = 1.7; 95% CI = 1.4–1.9) and having been connected to centres with outreach hepatitis care (OR = 1.4; 95% CI = 1.2–1.7). In people alive, HCV‐RNA+ prevalence was 31% if ever on OST or self‐reported injecting. Among HCV‐infected people, 69% were in drug use treatment at end of follow‐up. For participants entering the cohort after 2010, only 5% reported opiates as main drug of use and 17% had experience of injecting. Conclusion: Among Danish people in treatment for drug use from 1996 to 2015, receiving opiate substitution therapy had the largest associating to being tested for hepatitis C virus. As opiate use is declining, adapting test strategies will be necessary.